Chinese Traditional Thoughts Applied to Management and Education in the COVID-19 Era - Zhang, Dan; Emiliano T. Hudtohan (International Journal of Management and Education in Human Development, 2021)
We are wondering what is going on and what kind of world we will face after the COVID-19 pandemic. The COVID-19 pandemic has put large parts of the global economy on “pause”. The success of China in fighting with COVID-19 pandemic and the recovery of economy has been globally acknowledged. With long history and cultural heritage Chinese people integrate modern management principles with Chinese traditional thoughts to develop the unique approach to better monitoring and addressing management issues through the pandemic. The objective of the study aims to illustrate the framework and approach to effectively overcoming the difficulties of management and education in China during the COVID-19 pandemic. The primary method of this study is documentary research narrative (Marshall & Rossman, 2010) based on review of related literature in management. The conclusion of the study is suggested that the theory of Yin and Yang which teaches us that two opposing values and forces are related to each other in such a way of reconciliation that leads to harmony offers an effective principle of tradeoff for the relationship between management principles and Chinese traditional thoughts. Western management principles were supported by Chinese traditional thoughts as a response to create a unique managerial approach to dealing transparently and systemically with risk, uncertainty and irreversibility, such as the COVID-19 broke out. The traditional cultural values of the Chinese philosophers can drive the new perspective of management and education in the ASEAN for 21st century.